The effects of normobaric hypoxia on the leukocyte responses to resistance exercise - Allsopp, G.; Barnard, J.; Goodear, S.; Hoffmann, S.; Stephenson, G.; Addinsall, A.; Wright, C. (Biology of Sport, 2023)
There is growing interest in the use of systemic hypoxia to improve the training adaptations to resistance exercise. Hypoxia is a well-known stimulator of the immune system, yet the leukocyte responses to this training modality remain uncharacterised. The current study characterised the acute leukocyte responses to resistance exercise in normobaric hypoxia. The single-blinded, randomised trial recruited 13 healthy males aged 18-35 years to perform a bout of resistance exercise in normobaric hypoxia (14.4% O2; n = 7) or normoxia (20.9% O2; n = 6). Participants completed 4 × 10 repetitions of lower and upper body exercises at 70% 1-repetition maximum. Oxygen saturation, rating of perceived exertion and heart rate were measured during the session. Venous blood was sampled before and up to 24 hours post-exercise to quantify blood lactate, glucose and leukocytes including neutrophils, lymphocytes, monocytes, eosinophils and basophils. Neutrophils were higher at 120 and 180 minutes post-exercise in hypoxia compared to normoxia (p<0.01), however lymphocytes, monocytes, eosinophils and basophils were unaffected by hypoxia. Oxygen saturation was significantly lower during the four exercises in hypoxia compared to normoxia (p < 0.001). However, there were no differences in blood lactate, heart rate, perceived exertion or blood glucose between groups. Hypoxia amplified neutrophils following resistance exercise, though all other leukocyte subsets were unaffected. Therefore, hypoxia does not appear to detrimentally affect the lymphocyte, monocyte, eosinophil or basophil responses to exercise.